The Effectiveness of 3-2-1 Strategy Towards Students Reading Comprehension (Fakultas Ilmu Pendidikan Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
The purpose of this study is to know the effectiveness of a strategy of 3-2-1 at SMPN 5 Jombang in academic year of 2022/2023. The research method used is a pre experimental with model one group pre test and post test and with sample as much as 31 students. The result shows that there is a significant difference between pre-test and post-test. The study was obtained by calculating analytic data by using the t test, where the p-value or sig (2-tailed) = 0,000 is smaller than the degree of significance called sig a = 0.05. This outcome statistically means that hypothesis zero (Ho)is being denied. Thus, it can be said that strategy 3-2-1 is effective in students about reading comprehension.